The Diocesan Pastoral Council as an Instrument of Synodality: From Conciliar Vision to Canonical Norm - Komela Avan; Efraem Pea (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
This article presents a comprehensive historical-juridical analysis of the institutionalization of the Diocesan Pastoral Council. It traces the complex evolution of this body from the nascent, fragmented ideas that emerged during the preparations for the Second Vatican Council, through its significant conceptual and theological development during the conciliar sessions, to its normative crystallization in post-conciliar documents and its final, definitive codification in the 1983 Code of Canon Law. The analysis demonstrates that the Diocesan Pastoral Council was not a pre-conceived structure but the fruit of a gradual evolutionary process, representing an embryonic form of pastoral synodality, conceived to structurally foster the key elements of Communion, Participation, and Mission. This journey reflects the Council’s move away from a predominantly clerical and hierarchical model of the Church towards a richer vision of the Church as a Communion (Communio), emphasizing the shared dignity and co-responsibility of the entire People of God - clergy, religious, and laity - in the one mission of Christ. By meticulously examining the key documents, debates, and legislative formulations that shaped its identity, this paper argues that the Diocesan Pastoral Council stands as a primary and essential institutional expression of pastoral synodality at the diocesan level. It represents the successful translation of the highest theological principles of Vatican II into a concrete canonical structure designed to foster participation, dialogue, and collaborative discernment in the life of the particular Church.